Essence from within: Unveiling the voices of Nepalese master's degree students in English and biology education on internal assessments within the semester system - Shah, Rajendra Kumar; Paneru, Narendra Raj; Bohara, Bhuban Bahadur (Edelweiss Applied Science and Technology, 2024)
This study explores the changes in the examination system at Tribhuvan University, which originally adopted an annual examination system, switched to a semester system in 1971, and then reverted to the annual system in 1981. In 2013, the semester system was reintroduced, and it is now widely implemented across the university and other institutions in Nepal, although some undergraduate programmes still follow the annual system. These changes reflect ongoing efforts to reform the examination system, yet it remains unclear whether these reforms were based on comprehensive research and whether students’ experiences were adequately considered. The major objective of this study is to explore the lived experiences of Master’s degree students regarding internal assessments within the current semester system. A phenomenological approach was employed, with in-depth interviews conducted with eight students from the MEd English and Biology Education programmes at Tribhuvan University, Sanothimi Campus. The findings suggest that while the university has made significant strides in improving its educational and assessment systems, further improvements are necessary in the internal assessment procedures. Key areas for reform include enhancing student attendance, fostering more active classroom participation, involving students in research activities, and improving writing skills. Additionally, the study highlights the need for improvements in the quality of written examinations system and recommends that the curriculum be more aligned with real-world applications and focused on skill development.